A method to quantify the reduction of back and hip muscle fatigue of lift-support exoskeletons. (23rd January 2023) - van Sluijs, Rachel M.; Rodriguez-Cianca, David; Sanz-Morère, Clara B.; Massardi, Stefano; Bartenbach, Volker; Torricelli, Diego
Abstract: Cumulative back muscle fatigue plays a role in the occurrence of low-back injuries in occupations that require repetitive lifting of heavy loads and working in forward leaning postures. Lift-support exoskeletons have the potential to reduce back and hip muscle activity, thereby delaying the onset of fatigue in these muscles. Therefore, exoskeletons are being considered a potentially important tool to further reduce workload-related injuries. However, today no standards have been established on how to benchmark the support level of lift-support exoskeletons. This work proposes an experimental protocol to quantify the support level of a lift-support exoskeletons on instant changes in muscle activity and fatigue development while maintaining a static forward leaning posture. It then applies the protocol to experimentally assess the effect of the support provided by a commercially available lift-support exoskeleton, the LiftSuit 2.0 (Auxivo AG, Schwerzenbach, Switzerland), on the user. In a sample of 14 participants, the amplitude of the muscle activity of the back muscles (Δ_erectorspinae, thoracic0.35em =0.35em 33.0%, Δ_erectorspinae, lumbar0.35em =0.35em 13.2%) and hip muscles ( Δ_gluteusmaximus0.35em =0.35em 16.3% ) was significantly reduced. Wearing the exoskeleton significantly reduced the amount of fatigue developed during the task ( Δ_quadratuslumborum0.35em =0.35em 10.1%, Δ_gluteusmaximus0.35em =0.35em 44.0% ). Changes in muscle fatigue can be objectively recorded and correlated with relevant changes for exoskeleton users: the time a task can be performed and perceived low-back fatigue. Thus, including such measures of fatigue in standardized benchmarking procedures will help quantify the benefits of exoskeletons for occupational use.